Depression of Collateral Blood Flow Following Arterial Thrombosis - Schaub, Robert G.; Sande, Ronald; Meyers, Kenneth M. (Thrombosis and Haemostasis, 1977)
Permanent ligation of the feline aorta at the iliac bifurcation is followed by rapid opening of pre-existing collateral blood vessels. However, if ligation is combined with formation of a clot, these protective collateral vessels do not function. This study was undertaken to determine if drugs which alter serotonin function can improve collateral blood flow after arterial thrombosis. Permanent ligations were placed at the iliac bifurcation, circumflex iliac and sixth lumbar arteries in all cats. A clot was produced in the aorta of 27 cats by injection of 0.1 ml of thromboplastin. Ligated clot-occluded cats were untreated (10); had blood serotonin depleted using a single dose of reserpine (0.1 mg/kg i. m.) followed by para-chlorophenylanine (p-CPA) (100 mg/kg orally) every 3 days (9) ; or were treated prior to surgery with a serotonin antagonist cinanserin HC1 (4 mg/kg i. v.) (8). Control cats (18) were acutely ligated. 9 of these cats were untreated, 5 were cinanserin HC1-treated, and 4 were reserpine/p-CPA-treated. Extent of collateral development was assessed by aortograms 3 days after occlusion and by neurologic rating. Aortograms of acutely ligated cats indicated a significant collateral blood flow around the segment of ligated aorta, while ligated clot-occluded cats had a severely depressed hind-limb perfusion. Reserpine/p-CPA-treated ligation clot-occluded cats had aortograms similar to acutely ligated cats. The cinanserin HC1-treated ligation clot-occluded cats had aortograms which indicated hind-limb perfusion was not as adequate as the acutely ligated cats. However, the perfusion of these animals was improved over untreated ligation clot-occluded cats. Neurologic rating correlated with aortograms. These results suggest: 1) the clinical consequences of arterial thrombosis cannot be entirely attributed to mechanical occlusion of an artery, but may be due to depression of protective collateral blood flow induced by thrombosis, 2) serotonin is an important factor in this depression of collateral blood flow, and 3) isolation of the factors responsible for collateral inhibition could permit the development of therapeutic interventions.